The construction of happiness in volunteered work in environmental education in the municipal natural park of Nova Iguaçu-RJ - Queiroz, Edileuza Dias; Martins, Gabriel dos Santos (Revista Hipótese, 2018)
This article presents reflections about happiness, fluid feeling in contemporary society, discussing the close and necessary relationship between the construction of happiness and environmental education. Volunteering is a possibility for training based on the experiences of the collective in nature. Thus, we analyze a group of volunteers in a Conservation Unit and the reflection of this experience for the constitution of the social being, with Environmental Education as the intrinsic action of volunteering in these spaces.
Keywords: Happiness; Volunteering; Environmental education